Madrasas in the age of Islamophobia - Salam, Ziya Us (SAGE Publishing, 2019)
"In the age of Islamophobia, Madrasas are at crossroads-infamously labelled as 'dens for terrorism' where the 'youth are misguided, motivated and recruited to resort to anti-Indian activities'. It is little known that in the golden past, Madrasas schooled reformers and personalities such as Rajendra Prasad, Motilal Nehru, Raja Rammohun Roy and many other noteworthy Islamic scholars. Through bonafide stories of products of Madrasas, the authors narrate the decline of the madrasas from being centres of excellence to institutions of restricted learnings with dark clouds of stigma surrounding them. Short of resources, rejected by the well-heeled, and condemned by politicians, will they be able to turn the corner? The answer is blowing in the wind"--